SOSIALISASI POLITIK KPU PROVINSI JAWA BARAT DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR JAWA BARAT TAHUN 2018 - Nurzaman, Cecep; Yuningsih, Neneng Yani; Manan, Firman (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
This research analyzes the political socialization carried out by the West Java Provincial KPU against disability voter groups in the election of the Governor and Deputy Governor of West Java in 2018. This was motivated by the low level of participation in disability voters as well as the importance of opening political access rights for persons with disabilities. The theory used in this study is the theory of political socialization from Rush and Althoff where there are three methods, namely imitation, instruction and motivation. The method in this study is a qualitative method. The result of this research is the importance of political socialization to disability voters, because it is mandated by the 1945 Constitution and its derivative regulations and to realize an ideal democracy according to the criteria of voting equality and political socialization carried out by the West Java Provincial KPU to persons with disabilities to increase participation its politics with imitation methods, instruction and motivation.